Image of a person in Slobozhanskaya dialect phraseology: axiological measuring - Уманцева, Надія Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper deals with the important fragment of Slobozhanskaya phraseology, centered by the image of a person. Characteristics of the axiological parameterization of some of its features are found out in the context of the common cultural continuum of Ukrainians and their mentality. The axiological importance of those features which is in antonymous relations between themselves is accented. The constructive importance of mental and verbal stereotypes for the expression of a wide range of evaluation characteristics of a person is noted. Those dominant features and human characteristics which demonstrate its universal relevance for the people and which are determined by the peculiarities of its culture, word view and national mentality of the Ukrainians are found.